Lithium tetraborate single crystals as a substrate for SAW devices - FILIPIAK, J.; MAJCHROWSKI, A.; ŁUKASIEWICZ, T. (Archives of Acoustics, 1994)
Single crystals of lithium tetraborate (Li2B4O7) as a potential substrate for SAW devices have been investigated. Single crystals of lithium tetraborate have been grown according to the Czochralski technique. They combine a high electromechanical coupling coefficient for SAW with a small temperature coefficient of SAW velocity.